The Influence of Islam on Political Preferences in the 2024 Legislative Elections in Kampung Arab Manado - Deluhula, Prayogi Putra; Niode, Burhan; Mamentu, Michael (Dinasti Research, 2024)
Islam is an inseparable part of this nation, playing a massive role in the historical development of national civilization. As the country with the largest Muslim population in the world in 2023, Islam's influence on Indonesia, including its politics, is significant, particularly in political preferences. Within the abundance of Indonesia's resources lies the unique entity of Kampung Arab Manado, a Muslim community amidst a predominantly Christian population in Manado City. This article examines the influence of Islam on political preferences during the 2024 Legislative Elections in Kampung Arab Manado. This study employs a quantitative method (explanatory research) by conducting a simple regression analysis. The study's results indicate that the influence of Islam on political preferences in the 2024 Legislative Elections in Kampung Arab Manado yields a significance value of 0.000, which is smaller than the probability of 0.05. Therefore, the hypothesis of this study is accepted, confirming that there is an influence of Islam on political preferences in the 2024 Legislative Elections in Kampung Arab Manado. The magnitude of Islam's influence on political preferences reaches 13%, meaning that the higher the influence of Islam, the higher the political preference tendencies in the community. Additionally, if the value of Islam increases by 1%, it will increase political preferences by 0.697 in the 2024 Legislative Elections in Kampung Arab Manado.